ANALISIS PENDAPATAN USAHA TERNAK KAMBING KONTES DI PETERNAKAN NRJ FARM BOYOLALI TAHUN 2019–2021: ANALYSIS OF INCOME FROM CONTEST GOAT FARMING AT NRJ FARM BOYOLALI IN 2019–2021 - Damai Surya Wisma; Purwadi Purwadi; Eudia Christina Wulandari (Universitas Boyolali, 2026)
This study aimed to analyze the income and financial feasibility of contest goat farming at NRJ Farm Boyolali during 2019–2021. The background of this research is the growing trend of livestock contests in Indonesia as a platform for genetic selection and value-added livestock marketing. The methods included direct observation, interviews with the farm owner, and secondary data analysis from financial records. Parameters analyzed were Cost of Goods Sold (COGS), Net Profit, Break Even Point (BEP), Gross Profit Margin (GPM), and Return on Investment (ROI). The results showed that contest goat farming was financially feasible. Although the business was affected by the COVID-19 pandemic in 2020, it recovered in 2021 with a remarkable ROI of 217%. The success was supported by cost control, efficient variable cost management, and strategic herd expansion. It is concluded that the contest goat business in NRJ Farm is profitable and has potential for further development through income diversification and digital marketing strategies.